Business Communication Skills - Adelia; Khairunnisya, Nabila; Wardhana, Mada Aditia (Shofanah Media Berkah, 2026)
The critical role of multidimensional business communication skills in meeting professional demands in the era of the Industrial Revolution 4.0. This systematic literature review aims to analyze the effectiveness of innovative digital assessment tools and to identify the factors contributing to the competency gap between higher education graduates and industry expectations. The findings indicate that the implementation of digital assessment tools, such as vlog creation, is highly effective in developing complex communication abilities encompassing verbal, nonverbal, and digital literacy aspects. Conversely, the competency gap primarily stems from educational curricula that overly emphasize technical knowledge and a lack of awareness of professional communication standards. As a solution, pedagogical interventions based on self-efficacy through real-case simulations and mentor support are identified as crucial approaches to building students’ confidence and readiness. The review concludes that the integration of digital assessment and self-efficacy–based approaches is a vital strategy for bridging the competency gap and enhancing graduates’ relevance in a dynamic labor market.